miR824/AGAMOUS-LIKE16 Module Integrates Recurring Environmental Heat Stress Changes to Fine-Tune Poststress Development - Szaker, Henrik Mihály; Darkó, Éva; Medzihradszky, Anna; Janda, Tibor; Liu, Hsiang-chin; Charng, Yee-yung; Csorba, Tibor (Frontiers in Plant Science, 2019)
Abstract Plant development is continually fine-tuned based on environmental factors. How environmental perturbations are integrated into the developmental programs and how post-stress adaptation is regulated remains an important topic to dissect. Vegetative to reproductive phase change is a very important developmental transition that is complexly regulated based on endogenous and exogenous cues. Proper timing of flowering is vital for reproductive success. It has been shown previously that AGAMOUS LIKE 16 (AGL16), a MADS-box transcription factor negatively regulates flowering time transition through FLOWERING LOCUS T (FT), a central downstream floral integrator. AGL16 itself is negatively regulated by the microRNA miR824. Here we present a comprehensive molecular analysis of miR824/AGL16 module changes in response to mild and recurring heat stress. We show that miR824 accumulates gradually in response to heat due to the combination of transient transcriptional induction and post-transcriptional stability. miR824 induction requires HSE cis-elements and activity of the HSFA1 family and HSFA2 transcription factors. Parallel to miR824 induction, its target AGL16 is decreased, implying direct causality. AGL16 post-transcriptional repression during heat stress, however, is more complex, comprising of a miRNA-independent, and a miR824-dependent pathway. We also show that AGL16 expression is leaf vein-specific and overlaps with miR824 (and FT) expression. AGL16 downregulation in response to heat leads to a mild de-repression of FT. Finally, we present evidence showing that heat stress regulation of miR824/AGL16 is conserved within Brassicaceae. In conclusion, due to the enhanced post-transcriptional stability of miR824, stable repression of AGL16 is achieved following heat stress. This may serve to fine-tune FT levels and alter flowering time transition. Stress-induced miR824, therefore, can act as a ‘post-transcriptional memory factor’ to extend the acute impact of environmental fluctuations in the post-stress period.